2023
DOI: 10.3390/jof9020280
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Multigene Phylogeny Revealed Three New Species of Helminthosporium (Massarinaceae, Pleosporales) from China

Abstract: Saprobic hyphomycetes are highly diverse on plant debris. Over the course of our mycological surveys in southern China, three new Helminthosporium species, H. guanshanense sp. nov., H. jiulianshanense sp. nov. and H. meilingense sp. nov., collected on dead branches of unidentified plants, were introduced by morphological and molecular phylogenetic analyses. Multi-loci (ITS, LSU, SSU, RPB2 and TEF1) phylogenetic analyses were performed using maximum-likelihood and Bayesian inference to infer their taxonomic pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…There are many kinds of fungi in Jiangxi Province, and the fungal groups are complex. Relevant studies have shown that several mycological investigations are also constantly exploring and enriching the fungal diversity (e.g., [12,[43][44][45][46]). In this study, we isolated plant pathogens from diseased leaves of a wide range of plant hosts in Jiangxi Province, China.…”
Section: Discussionmentioning
confidence: 99%
“…There are many kinds of fungi in Jiangxi Province, and the fungal groups are complex. Relevant studies have shown that several mycological investigations are also constantly exploring and enriching the fungal diversity (e.g., [12,[43][44][45][46]). In this study, we isolated plant pathogens from diseased leaves of a wide range of plant hosts in Jiangxi Province, China.…”
Section: Discussionmentioning
confidence: 99%